The Presence and the Role of Senses in Proto-Apocalyptic Book of Joel - Nowińska, Joanna (The Biblical Annals, 2026)
The proto-apocalyptic Book of Joel attracts attention with a multitude of sensory references. They not only provide the dynamics of the text but also create an experience of interpersonal contact that is elusive in cursory reading. The synergy in which they remain and the mutual reinforcement raise the question of the role of the senses in the process of persuasion undertaken in the apocalyptic context and text. Analyses of the semantic layer, with the application of the methods of literary analysis, with reference also to the theory of affect, conducted on the biblical text in synchronicity, reveal the radical turns of thought, marked by references to the senses, as well as counterpoints highlighting the main points of the message. They make it possible to perceive the various stages of the communicative exchange, its coherence, and the specificity of affect, where the removal of blockages in the interpersonal relationship is located. The application of the guidelines of the theory of affect reveals, among other things, the space of perception offered in the Book of Joel through references to the senses, in accordance with the culture of the recipient. The power of persuasion, pointing to the active work of God, conveyed through the language of the senses, becomes graspable to the recipient who experiences trauma and adversity.